Digital Storage of Notarial Deed Minutes in Society 5.0. - Maulana Ibrahim Patahna; Herlindah; Heru Ratno Hadi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2027)
The development of information technology in the Society 5.0 era has accelerated digital transformation across various sectors, including the management of notarial records. This study aims to analyze the urgency of regulating the digital storage of notarial deed minutes and to formulate an ideal legal framework for such regulation within the Indonesian legal system. This research employs a normative legal method using statutory, conceptual, and comparative approaches by examining the Law on Notarial Office, the Electronic Information and Transactions Law, the Personal Data Protection Law, and regulations governing electronic systems. The research gap lies in the absence of a comprehensive study integrating the analysis of regulatory gaps, normative inconsistencies, and the formulation of a regulatory model for digital storage of notarial deed minutes within the framework of notarial law reform. Previous studies have generally focused only on the legality of cyber notary practices, the validity of electronic documents, or digital storage as a data backup mechanism. The findings indicate that the digital storage of notarial deed minutes lacks an adequate legal basis because the Law on Notarial Office still recognizes only physical storage, while the electronic document regime excludes notarial deeds. This situation creates regulatory gaps, legal uncertainty, and juridical, technical, and ethical risks in notarial practice. The novelty of this study lies in proposing a regulatory model integrating legal certainty, legal protection, data security, electronic system accountability, and regulatory harmonization as the foundation for notarial law reform. The study recommends the enactment of comprehensive regulations to support a secure, effective, and sustainable digital notarial system in Indonesia.